Pelatihan Pengembangan Usaha Jagung dan Singkong Bagi Masyarakat di Desa Pringgesele Lombok Timur - Irwan Suriadi; Siti Sriningsih; Hailudin Hailudin; Gusti Ayu Arini; Baiq Saripta Wijimulawiani (Universitas Mataram, 2021)
The purpose of this program is to help partners to process corn and cassava agricultural products from raw products into high value and high value added products that will increase income for the people in the Pringgese village. The method used in achieving the objectives of this activity is by conducting training and assistance. The results of community service activities are that people in the village of Pringgesele can develop high-value processed corn and cassava products so as to increase the income of the people in the village of Pringgesele by processing raw materials in the form of corn and cassava into finished goods that have added value and can open jobs for the community around with the existence of processed corn and cassava products because so far the yield of agricultural products in the form of corn and cassava is quite a lot in the village of Pringesele.